Using FOP for industrial needs how to ensure accuracy at the client tier. - Zade, Rajesh
The Web has given us an easy-to-use, easy-to-market, and easy-to-navigate medium for conducting business. We've come to a stage where mainstream people are comfortable shopping on the Web. What it lacks is the ability to ensure that what the end user has browsed or accepted is the same as what was processed on the back end. In other words, how do you make sure the confirmation of a transaction is the same as the transaction itself?